Administration of the Interleukin-1 Inhibitor Canakinumab in Children with Autoinflammatory Diseases and Systemic Juvenile Arthritis: the Report for Case Series - S. O. Salugina; M. I. Kaleda; Ye. S. Fyodorov; I. P. Nikishina ("Paediatrician" Publishers LLC, 2016)
In Russia, the interleukin-1 inhibitor canakinumab (fully human monoclonal antibodies to interleukin-1) is increasingly used for treating autoinflammatory diseases and systemic juvenile arthritis (sJIA). The article describes the experience of administering canakinumab in patients with autoinflammatory diseases (n = 12) and sJIA (n = 7), the efficacy and tolerability of the drug are analyzed. Canakinumab was prescribed subcutaneously in a dose of 2-6 mg/kg (maximum 300 mg) once in 4-8 weeks. The therapy duration ranged from 3 months to 4 years. All patients had a rapid clinical improvement, relief of systemic manifestations, normalization of the level of acutephase inflammatory markers. In 4 patients with sJIA we failed to achieve the relief of arthritis symptoms. While administering the drug, no serious adverse events were registered. Thus, the experience of administering canakinumab in patients with autoinflammatory diseases and sJIA showed the high efficacy and good tolerability of the drug. The canakinumab administration at sJIA can be effective in the early disease stages in patients with systemic and initial articular changes.